Effects and safety of Ginkgo biloba on blood metabolism in type 2 diabetes mellitus: a systematic review and meta-analysis - Zou, Huimin; Fang, Jingxian; Han, Yu; Hu, Xue; Meng, Jian; Huang, Fang; Xu, Hui; Lu, Chengfei; Wang, Yiwen; Zhang, Lili; Dong, Xiaohong; Yu, Yanmei; et al. (Frontiers in Endocrinology, 2024)
Background：There existed controversy in Ginkgo biloba (GKB) on blood metabolism among type 2 diabetes mellitus(T2DM) patients, and we tried to analyze the effects and safety of GKB on T2DM patients. Methods：We conducted literature search between January 2003 and December 2022 in 7 online databases (PubMed, Scopus, Embase, Google Scholar, Web of Sciences, Cochrane Library and China National Knowledge Infrastructure). A systematic literature review and meta-analysis was performed to compare effects and safety of GKB among T2DM patients. Four groups of parameters were extracted and analyzed including hemorheology parameters, lipid profile, glycemic control markers and adverse events. Results：In the end, 13 eligible articles with 11 indicators among 1573 patients were included. In hemorheology parameters section, GKB had significant lower plasma viscosity (PV) (SMD=-0.91, 95%CI [-1.45, -0.36], P<0.01) and hematocrit (Hct) (SMD=-0.60, 95%CI [-0.97, -0.24], P<0.01) than control group. GKB had higher velocity of dorsalis pedis artery (VDPA) (SMD=0.51, 95%CI [0.26, 0.76], P<0.01) and ankle brachial index (ABI) (SMD=0.71, 95%CI [0.32, 1.10], P<0.01) than control. In both lipid profile and glycemic control markers sections, we did not find any difference between GKB and control groups, including total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), hemoglobin A1c (HbA1c) and fasting serum glucose (FSG). In addition, there was no difference of adverse events (AE). The sensitivity analysis and funnel plot showed that the results in this research was robust and had no publication bias. Conclusion：In conclusion, GKB might safely reduce the risk of peripheral arterial or even systemic cardiovascular disease. But GKB did not directly improve lipid and blood glucose levels in T2DM patients.